Biglycan neo-epitope (BGN262), a novel biomarker for screening early changes in equine osteoarthritic subchondral bone. Issue 10 (October 2022) - Adepu, S.; Ekman, S.; Leth, J.; Johansson, U.; Lindahl, A.; Skiöldebrand, E.
Summary: Objective: Native biglycan (BGN), which can undergo proteolytic cleavage in pathological conditions, is well known to be involved in bone formation and mineralization. This study aimed to delineate the specific cleavage fragment, a neo-epitope for BGN (BGN 262 ), in synovial fluid (SF) from young racehorses in training, osteoarthritic (OA) joints with subchondral bone sclerosis (SCBS), and chip fracture joints. Design: A custom-made inhibition ELISA was developed to quantify BGN 262 in SF. Cohort 1: A longitudinal study comprising 10 racehorses undergoing long-term training. Cohort 2: A cross-sectional study comprising joints from horses ( N = 69) with different stages of OA and radiographically classified SCBS. Cohort 3: A cross-sectional study comprising horses ( N = 9) with chip fractures. Receiver operating characteristic (ROC) curve analysis was performed (healthy joints vs chip joints) to evaluate BGN 262 robustness. Results: Cohort 1: SF BGN 262 levels from racehorses showed a statistical increase during the first 6 months of the training period. Cohort 2: BGN 262 levels were significantly higher in the SF from severe SCBS joints. Cohort 3: SF BGN 262 levels in chip fracture joints showed a significant increase compared to normal joints. The ROC analysis showed an AUC of 0.957 (95% C.I 0.868–1.046), indicating good separation between the groups. Conclusions: The data presented show that BGN 262 levels increase in SF in correlation with the initiation of training, severity of SCBS, and presence of chip fractures. This suggests that BGN 262 is a potential predictor and a novel biomarker for early changes in subchondral bone (SCB), aiming to prevent catastrophic injuries in racehorses.